USING CORPORATE MECHANISMS TO IMPROVE ACADEMIC ENGLISH LANGUAGE PROFICIENCY AMONG POSTGRADUATE STUDENTS: IMPACT ON THE LEARNING PROCESS - Ольга Володимирівна Чайковська (Відкрите освітнє е-середовище сучасного університету)
A high level of proficiency in academic English is a prerequisite for the successful functioning of postgraduate students in the scientific and educational environment. This includes an accurate presentation of scientific ideas in both written and oral forms, presentation of research results at international events, access to publications in world scientometric databases and the ability to publish one's work. In the modern educational context, technologies, in particular concordancers, play an important role in developing academic foreign language competence and forming independent work skills. The study aimed to assess the effectiveness of the use of concordancers (AntConc and Lextutor) in the formation of academic foreign language competence of postgraduate students in the speciality Agronomy and to compare them with alternative means - online resources and applications based on artificial intelligence (Academic Phrasebank, Google Scholar Tools, Grammarly, ChatGPT). The study involved 30 first-year postgraduate students divided into experimental and control groups. The methodology included diagnostic (pre-test) and final (post-test) testing, which covered theoretical questions, analysis of a fragment of a scientific text and writing an essay in a scientific style. Statistical processing of the results was carried out using the Student's t-test. In addition, students filled out a questionnaire with open and closed questions, which were analyzed quantitatively and using the open coding method.